Elevated uric acid is related to the no‐/slow‐reflow phenomenon in STEMI undergoing primary PCI. (26th November 2021) - Hu, Xiangming; Yang, Xing; Li, Xida; Li, Guang; Zhou, Yingling; Dong, Haojian
Abstract: Background: No‐/slow‐reflow phenomenon (NRP) is a severe complication in patients with ST‐segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (pPCI). This study aimed to explore the relationship between elevated serum uric acid (SUA) and NRP in patients with STEMI undergoing pPCI, focusing on inflammation and angiographic findings. Methods: A total of 610 patients who received pPCI for STEMI were retrospectively enrolled. Patients were divided into a hyperuricaemia group and a non‐hyperuricaemia group according to SUA levels. Clinical information and angiographic indicators were compared between the two groups. Thrombolysis in myocardial infarction (TIMI) flow and TIMI myocardial perfusion grade (TMPG) <3 after stent implantation were defined as TIMI‐NRP and TMPG‐NRP, respectively. A logistic model was used to analyse the relationship between hyperuricaemia and NRP. Results: The hyperuricaemia group had a higher incidence of TIMI‐NRP (24.9% vs 14.0%, p < .001) and TMPG‐NRP (33.0% vs 24.9%, p = .03), higher levels of C‐reactive protein (7.2 vs 4.1 mg/L, p < .001) and worse left ventricular ejection fraction (51.5% vs 54.0%, p = .002) than the non‐hyperuricaemia group. As for angiographic findings, there was no significant difference between the two groups in terms of lesion characteristics measured by quantitative coronary angiography. After multivariable adjustment, elevated SUA was significantly associated with TIMI‐NRP (odds ratio: 1.94, 95% confidence interval: 1.24–3.01, p = .003). Subgroup analysis showed that the effect of hyperuricaemia in TIMI‐NRP was more pronounced in patients with delayed perfusion as well as in patients with diabetes mellitus. Conclusions: Elevated SUA is associated with severe inflammation and has higher incidence of TIMI‐NRP in patients with STEMI undergoing pPCI, especially in those with delayed perfusion or diabetes mellitus.